Extramedullary hematopoiesis is associated with lower cardiac iron loading in chronically transfused thalassemia patients. Issue 11 (8th October 2015) - Ricchi, Paolo; Meloni, Antonella; Spasiano, Anna; Neri, Maria Giovanna; Gamberini, Maria Rita; Cuccia, Liana; Caruso, Vincenzo; Gerardi, Calogera; D'Ascola, Domenico Giuseppe; Rosso, Rosamaria; Campisi, Saveria; Rizzo, Michele; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate, in a large cohort of chronically transfused patients, whether the presence of extramedullary hematopoiesis (EMH) accounts for the typical patterns of cardiac iron distribution and/or cardiac function parameters. We retrospectively selected 1, 266 thalassemia major patients who had undergone regular transfusions (611 men and 655 women; mean age: 31.3 ± 8.9 years, range: 4.2–66.6 years) and were consecutively enrolled within the Myocardial Iron Overload in Thalassemia network. The presence of EMH was evaluated based on steady‐state free precession sequences; cardiac and liver iron overloads were quantified using a multiecho T2* approach; cardiac function parameters and pulmonary diameter were quantified using the steady‐state free precession sequences; and myocardial fibrosis was evaluated using the late gadolinium enhancement technique. EMH was detected in 167 (13.2%) patients. The EMH+ patients had significantly lower cardiac iron overload than that of the EMH− patients (P = 0.003). The patterns of cardiac iron distribution were significantly different in the EMH+ and EMH− patients (P < 0.0001), with a higher prevalence of patients with no myocardial iron overload and heterogeneous myocardial iron overload and no significant global heart iron in the EMH+ group EMH+ patients had a significantly higher left ventricle mass index (P = 0.001) and a significantly higher pulmonary artery diameter (P = 0.002). In conclusion, in regularly transfused thalassemia patients, EMH was common and was associated with a thalassemia intermedia‐like pattern of cardiac iron deposition despite regular transfusion therapy. Am. J. Hematol. 90:1008–1012, 2015. © 2015 Wiley Periodicals, Inc.